Evaluation of Fiscal Corrections on Operating Expenses and Other Income in the Annual Corporate Tax Return Reporting of CV XYZ - Qomariyah, Faizatul; Putri Vizandra, Ellyzabeth (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study aims to evaluate the application of fiscal corrections to operating expenses and other income in the Annual Corporate Tax Return (SPT) reporting of CV XYZ. The background of this research is based on the differences in treatment between commercial financial statements prepared in accordance with Financial Accounting Standards (SAK) and tax regulations, which require fiscal corrections to determine the appropriate taxable income. The method used in this study is descriptive qualitative, with data analysis techniques in the form of narrative analysis of financial statements and applicable tax regulations. The results show that several accounts, such as internet expenses, Article 21 income tax, and interest income from bank deposits, need to be corrected, as they are not fully recognized under tax regulations. Therefore, fiscal corrections play a crucial role in ensuring tax compliance and the accuracy of the company’s fiscal financial statements.